Leadership for the Future Sustainable Development of Business and Education 2017 Prague Institute for Qualification Enhancement (PRIZK) and International Research Centre (IRC) "Scientific Cooperation" International Conference (Springer Proceedings in Business and Economics,, 2018)
This proceedings volume examines leadership from the perspectives of business, economics, social sciences, cross-cultural management, and education as a means to establish a future of sustainable development. Featuring contributions from the 2017 Prague Institute for Qualification Enhancement (PRIZK) and International Research Centre (IRC) "Scientific Cooperation" International Conference held in the Czech Republic, this volume focuses particularly on business models and higher education schemes from BRICS nations and examines topics such as social and educational practices, academic policies and business development. Leadership is becoming a key element for the future sustainable development of business and education in the quickly globalizing world. In this regard, a special emphasis should be made on the formation of high-quality human resources-the leading experts in their field who will create innovations and introduce breakthrough technologies. The development of a creative economy and knowledge economy requires highly-educated human capital, thus education becomes a key element of this process. Education must keep pace with time, be competitive, and stay in touch with the process of technology. The enclosed papers identify the key steps for sustainable growth and development in business and education. Featuring contributions on theory and practice, this book is appropriate for academics, researchers, policy-makers and practitioners in the areas of business, leadership management, entrepreneurship, innovation and education. .